PATENTS AS FIDUCIARY COLLATERAL IN BANK CREDIT - I Gusti Agung Ayu Patrecia Marthavira (NOTARIIL Jurnal Kenotariatan, 2020)
The aims of this study are to determine the regulation of patents as fiduciary guarantees in bank credit and find out how to assess the economic value of patents as fiduciary guarantees. This study used statute approach and conceptual approach. This research method used three sources of legal materials, namely primary legal materials, secondary legal materials, and tertiary legal materials. The legal material collection is done through library research The main legal material obtained from the field was first examined for completeness and clarity to be classified as well as systematic and consistent preparation to facilitate analysis. Secondary legal material was obtained from the literature and was collected systematically, so that it could be used as a reference in conducting analysis. The results of the legal material were carried out with library and field research, as well as descriptive analytical discussions. The results of this study are the regulation of patents as fiduciary guarantees in bank credit contained in Article 108 paragraph (1) of Law Number 13 Year 2016 concerning Patents which determines that the right to a Patent can be used as an object of fiduciary security. Patents include intangible movable property that can be transferred or transferred because of a written agreement. How to assess the economic value of patents as fiduciary guarantees, namely the market approach, income approach and cost approach.